BCR‐ABL tyrosine kinase inhibitors promote pathological changes in dilator phenotype in the human microvasculature. (5th September 2020) - Durand, Matthew J.; Hader, Shelby N.; Derayunan, Alexa; Zinkevich, Natalya; McIntosh, Jennifer J.; Beyer, Andreas M.
Abstract: Objective: Treatment with BCR‐ABL tyrosine kinase inhibitors (TKIs) is the standard of care for patients with chronic myeloid leukemia, however evidence indicates these compounds may have cardiovascular side‐effects. This study sought to determine if ex vivo exposure of human adipose arterioles to the BCR‐ABL TKIs imatinib and nilotinib causes endothelial dysfunction. Methods: Human adipose arterioles were incubated overnight in cell culture media containing vehicle (PBS), imatinib (10 µmol/L) or nilotinib (100 µmol/L). Arterioles were cannulated onto glass pipettes and flow mediated dilation (FMD) was assessed via video microscopy. To determine the mechanism of vasodilation, FMD was re‐assessed in the presence of either the nitric oxide synthase inhibitor L‐NAME (100 µmol/L) or the H2 O2 scavenger PEG‐Catalase (500 U/mL). Results: Neither imatinib nor nilotinib affected the magnitude of FMD (max dilation = 78±17% vehicle, 80 ± 24% nilotinib, 73 ± 13% imatinib). FMD was decreased by L‐NAME in vehicle‐treated arterioles (max dilation = 47±29%). Conversely, L‐NAME had no effect on FMD in imatinib‐ or nilotinib‐treated vessels (max dilation = 79±14% and 80 ± 24%, respectively), rather FMD was inhibited by PEG‐Catalase (max dilation = 29±11% and 29 ± 14%, respectively). Conclusion: Incubating human arterioles with imatinib or nilotinib switches the mediator of FMD from vasoprotective nitric oxide to pro‐inflammatory H2 O2 .